Biology of Red Palm Mite, Raoiella indica, on Different Coconut Varieties - Aulia Nusantara; Y. Andi Trisyono; Suputa Suputa; Edhi Martono (Universitas Gadjah Mada, 2017)
Red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae), has emerged as a new threat to coconut plantation in Indonesia. To control this mite, understanding on its biology is essential. The effects of three coconut varieties (Salak Dwarf, Local Sumenep Tall, and Hybrid coconuts) on the development and fecundity of R. indica were determined under laboratory conditions at 26−28oC, 80% RH, and photoperiod of 12:12 (L:D). The life cycle of R. indica consisted of the egg, larva, protonymph, deutonymph, and adult stages. Total development time of immature females was significantly influenced by coconut varieties. The shortest immature developmental time occurred at Salak Dwarf variety (26.07 days), whereas no significant difference of development time of immature female on Hybrid and Local Sumenep Tall varieties was found. Moreover, there was also no significant difference on the development time of immature male and on the fecundity of the mite among different coconut varieties. IntisariTungau merah kelapa, Raoiella indica Hirst (Acari: Tenuipalpidae), merupakan ancaman baru bagi perkebunan kelapa di Indonesia. Pemahaman mengenai biologi diperlukan untuk strategi pengendalian tungau tersebut di masa datang. Pengaruh tiga varietas kelapa yang berbeda (Genjah Salak, Lokal Sumenep, dan Hibrida) terhadap perkembangan dan keperidian R. indica diamati pada kondisi laboratorium dengan suhu 26−28oC, kelembapan nisbi 75−85%, serta pencahayaan 12 jam terang dan 12 jam gelap (L:D=12:12). Siklus hidup tungau terdiri dari telur, larva, protonimfa, deutonimfa, dan dewasa. Hasil pengujian menunjukkan bahwa waktu perkembangan betina pradewasa dipengaruhi secara nyata oleh varietas kelapa. Waktu perkembangan paling pendek terdapat pada kelapa Genjah Salak (26,07 hari), sedangkan waktu perkembangan betina pradewasa tidak berbeda nyata pada kelapa Hibrida dan Dalam Lokal Sumenep. Hasil lain pengujian menunjukkan tidak terdapat perbedaan nyata waktu perkembangan jantan pradewasa dan keperidian pada ketiga varietas.